Variasi Ukuran Payudara sebagai Daya Tarik Fisik Perempuan di Masyarakat Lampung - Winati Nurhayu; Eri Luxiana; Andy Darmawan; Jeane Siswitasari Mulyana; Gres Maretta (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Sexual selection occurs when living organisms, including humans, exhibit specific preferences for morphological traits related to health and fertility when choosing a mate. Various physical characteristics such as body size and shape, leg length, skin color, hair length and color, facial features, and breast size contribute to the physical attractiveness of females in mate selection. Breasts can serve as a particular attraction for males, as they are believed to be associated with health and fertility for reproductive purposes. Sexual selection leads to a range of breast sizes, from small to large, within a population. The aim of this research is to investigate the variation in breast size preferences among females in the Indonesian society, specifically in Lampung. The study was conducted by distributing both online and offline questionnaires randomly with breast size stimuli in the form of images. Descriptive data analysis was employed to examine the variation in breast size preferences. Very large breast sizes were considered healthy and feminine by respondents, while medium sizes were deemed attractive. Married male respondents preferred larger breast sizes on average compared to unmarried respondents. Higher-income respondents tended to select larger breast sizes. Respondents with lower educational backgrounds tended to prefer smaller breast sizes. Respondents residing in rural areas preferred larger breast sizes compared to those living in urban areas. In conclusion, sexual selection applied among the population of Lampung in the context of breast size preferences.